Caractérisation des calcaires des gisements d’El Hadjeb et de Koudiet El Khechba (W. de Bouira) et estimation de ses réserves exploitables par deux méthodes numériques - ARAB ,Lynda; BOURAI, Hanane; DASSAMIOUR ,Mohamed (Encadreur ) (Université Ferhat Abbas Sétif 1. institut d'architecture et sciences de la terre. département de géologie, 2018)
In this study, two new methods were used to calculate the exploitable limestone reserves of El Hadjeb quarry and the new Koudiet El Khecheba quarry of ENG. A comparative study on the limestones of the two sites, based on geochemical and geotechnical analysis data, made it possible to characterize these aggregates which have similar characteristics. The evaluation study of the exploitable reserves of the two quarries was carried out by two volumetric methods; the trapezium method and the Simpson method, which had given very similar results. This is can be explained by the simple structure and morphology which does not show strong topography irregularities
في هذه الدراسة ، تم استخدام طريقتين جديدتين لحساب احتياطيات الحجر الجيري القابلة للاستغلال في محجره الحاجب ومحجره كدية الخشبة الجديد التابع لشركة ENG . وقد أتاحت دراسة المقارنة على الحجر الجيري للموقعين ، استنادا إلى بيانات التحليل الجيوكيميائي والجيوتقني ، إثبات بأن الحجر الجيري للموقعين له خصائص متشابهة. دراسة تقدير الاحتياطيات القابلة للاستغلال في المحرجتين بالطريقتين الحجميتين ؛ طريقة شبه المنحرف وطريقة سيمبسون, أعطت نتائج مشابهة جدا. ويوضح ذلك التضاريس البسيطة التي لا تظهر مفارقات كبيرة
Keywords: Carrière d'El Hadjab; Carrière de Koudiet El Khacheba; granulats; Réserve en calcaire; caractéristique; simpson; trapéze